"The Teaching of These Words": Intertextuality, Social Identity, and Early Christianity : Essays in Honor of Clayton N. Jefford - Draper, Jonathan A.,; Pardee, Nancy D.,; Wilhite, Shawn J., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
What does it mean for a group to speak of its identity and, in contrast, to speak about the "other"? As with all groups, early Christian communities underwent a process of identity formation, and in this process, intertextuality played a role. The choice of biblical texts and imageries, their reception and adaptation, affected how early Christian communities perceived themselves. Conversely, how they perceived themselves affected which texts they were drawn to and how they read and received them. The contributors to this volume examine how early Christian authors used Scripture and related texts and, in turn, how those texts shaped the identity of their communities.